Exploiting IoT and LoRaWAN Technologies for Effective Livestock Monitoring in Nigeria - Abdullahi, U. S.; Nyabam, M.; Orisekeh, K.; Umar, S.; Sani, B.; David, E.; Umoru, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
With global population predicted to rise continuously (from 7.2 billion to between 9~10 billion people by the year 2050), the world would need to produce almost twice the amount of food as it does today to sustain such human needs. This coupled with recent environmental/climatic changes and urbanization would continue to place enormous burden on the available land, water and energy resources required for both crop and animal farming which is even more critical for developing regions, such as Sub-Saharan Africa due to arid lands, poverty, extreme hunger and endemic diseases. Hence, there is an urgent need for more effective, intensification and industrialization of the region’s agricultural sector to improve food supply. Internet-of-things (IoT) is a new and attractive family of technologies capable of modernizing Africa’s agricultural sector in line with best practices to improve productivity and minimize cost with reduced energy consumption. This paper intends to kick-start discussions around IoT-based solutions in livestock farming in Nigeria, with a view to addressing issues of cattle rustling as well as improved livestock health-care and better herd management through real-time monitoring. The proposed solution leverages LoRaWAN (Long-range Wireless Access Network) technology, whereby very low-power sensors with extremely long-range are attached to the cattle, and communicate with a gateway for linking to the cloud/satellite network to the internet for data processing and analytics. Such a system is also ideal for rural/remote areas where there is limited or no cellular network and internet coverage, which is where most Nigerian farms/ranches may be located.  The paper sheds some light on some real-life use cases, benefits and challenges of deploying such smart systems and provides some recommendations/action points for all relevant stake-holders towards a sustainable implementation in Nigerian agricultural sector